In vitro toxicity of beauvericin alone and combined with fumonisin B1 or deoxynivalenol on Caco-2 cells (International Journal of Health, Animal Science and Food Safety, 2016)
Beauvericin (BEA) is a mycotoxin produced by Fusarium species, frequently occurring in cereal grains in combination with fumonisin B1 (FB1) and deoxynivalenol (DON). The aim of this study was to evaluate the in vitro toxic effects of BEA alone and combined with FB1 or DON on human intestinal Caco-2 cells cultured on semi-permeable inserts (Caloni et al., 2012). Caco-2 cells were treated for 24 h with BEA (1.5 μM) alone and combined with FB1 (1.5 μM) or DON (3.5 μM) on both apical (Ap) and basolateral (Bl) sides. Barrier impairment was assessed by measuring the trans-epithelial electrical resistance (TEER) after 1 h, 2 h and 24 h of treatment. At the end of the experiment, the culture medium was collected for interleukin-8 (IL-8) determination. The results indicate that TEER was not significantly affected by Ap or Bl exposure to BEA and FB1 alone, whereas a significant decrease (P
Keywords: Beauvericin; Caco-2 cells; Deoxynivalenol; Fumonisin B1; Toxicity